Arrhythmogenic Right Ventricular Cardiomyopathy: Characterization of Left Ventricular Phenotype and Differential Diagnosis With Dilated Cardiomyopathy. Issue 5 (3rd March 2020) - Cipriani, Alberto; Bauce, Barbara; De Lazzari, Manuel; Rigato, Ilaria; Bariani, Riccardo; Meneghin, Samuele; Pilichou, Kalliopi; Motta, Raffaella; Aliberti, Camillo; Thiene, Gaetano; McKenna, William J.; Zorzi, Alessandro; et al.
Abstract : Background: This study assessed the prevalence of left ventricular (LV) involvement and characterized the clinical, electrocardiographic, and imaging features of LV phenotype in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC). Differential diagnosis between ARVC‐LV phenotype and dilated cardiomyopathy (DCM) was evaluated. Methods and Results: The study population included 87 ARVC patients (median age 34 years) and 153 DCM patients (median age 51 years). All underwent cardiac magnetic resonance with quantitative tissue characterization. Fifty‐eight ARVC patients (67%) had LV involvement, with both LV systolic dysfunction and LV late gadolinium enhancement (LGE) in 41/58 (71%) and LV‐LGE in isolation in 17 (29%). Compared with DCM, the ARVC‐LV phenotype was statistically significantly more often characterized by low QRS voltages in limb leads, T‐wave inversion in the inferolateral leads and major ventricular arrhythmias. LV‐LGE was found in all ARVC patients with LV systolic dysfunction and in 69/153 (45%) of DCM patients. Patients with ARVC and LV systolic dysfunction had a greater amount of LV‐LGE (25% versus 13% of LV mass; P <0.01), mostly localized in the subepicardial LV wall layers. An LV‐LGE ≥20% had a 100% specificity for diagnosis of ARVC‐LV phenotype. An inverse correlation between LV ejection fraction and LV‐LGE extent was found in the ARVC‐LV phenotype ( r =−0.63; P <0.01), but not in DCM ( r =−0.01; P =0.94). Conclusions: LV involvement in ARVC is common and characterized by clinical and cardiac magnetic resonance features which differ from those seen in DCM. The most distinctive feature of ARVC‐LV phenotype is the large amount of LV‐LGE/fibrosis, which impacts directly and negatively on the LV systolic function.